Advances in Health and Environment Safety Select Proceedings of HSFEA 2016 (Springer Transactions in Civil and Environmental Engineering,, 2018)
This book comprises selected papers on advances in the field of health and environment safety that were presented at the leading international conference on advances in the field of health, safety, fire, environment, allied sciences and engineering (HSFEA 2016). The book focuses on the latest developments in the field of health and environment safety, and highlights related opportunities and challenges. The book also presents methods that can be used to effectively monitor and measure climate change and global warming. Further, the contents of this work stress the importance of maintaining safety and healthy work environments that are free of occupational health hazards. This book will be of interest to researchers, professionals, and policy makers alike.